Pelatihan Adzan Menggunakan Irama Jiharkah Untuk Menumbuhkan Minat Anak Dalam Mengumandangkan Adzan di Majelis Ar-Rahim - Ardan Nalapraya; Rika Purnamasari; Usep Setiawan (CV. Devi Tara Innovations, 2025)
This research location faces the problem of children’s lack of interest in calling to prayer. This has led to a lack of attendance among children during prayers at the mosque, which is feared to be sustainable. This community service aims to increase children’s interest and awareness in calling to prayer at the mosque with an approach using the Jiharkah rhythm. Jiharkah is one of the seven rhythms that are often used in Indonesia. The method used is the PAR (participatory action research) method, which involves the community actively in every stage of the activity. The results of this service showed an increase in children’s understanding and confidence in calling to prayer. They began to practice the learning that had been done in the training program.